The Influence of Interest Rates, Inflation, Exchange Rates and Exports on Indonesia's Foreign Exchange Reserves - Ratnaningtyas, Anindya Hastuti; Huda, Syamsul (Indonesian Journal of Business Analytics, 2023)
Inconsistencies between changes in foreign exchange reserves and interest rates, inflation, export value, and the Rupiah exchange rate versus the US Dollar were revealed by this research. The aim is to determine how Indonesia's foreign exchange reserves are affected by interest rates, inflation, exchange rates and exports. This research uses descriptive quantitative methods with an explanation strategy. The research was conducted using secondary data from Bank Indonesia and the Indonesian Central Statistics Agency for the period 2005–2021, with a sample of 11 data taken using the selective selection method. Through IBM SPSS version 23, multiple linear regression was used to analyze the data. The findings show that while exports have a sizable positive impact on foreign currency reserves, interest rates have a significant negative impact. However, there is little impact on foreign exchange reserves from inflation and the exchange rate. In conclusion, these factors together have a big impact on Indonesia's foreign exchange reserves: interest rates, inflation, exchange rates, and exports.